Defining aggressive or early progressing nononcogene-addicted non-small-cell lung cancer: a separate disease entity?. (13th February 2019) - Reck, Martin; Kerr, Keith M; Grohé, Christian; Manegold, Christian; Pavlakis, Nick; Paz-Ares, Luis; Huber, Rudolf M; Popat, Sanjay; Thatcher, Nick; Park, Keunchil; Hilberg, Frank; Barrueco, José; et al.
A substantial proportion of patients with nononcogene-addicted non-small-cell lung cancer (NSCLC) has 'aggressive disease', as reflected in short time to progression or lack of disease control with initial platinum-based chemotherapy. Recently, clinical correlates of aggressive disease behavior during first-line therapy have been shown to predict greater benefit from addition of nintedanib to second-line docetaxel in adenocarcinoma NSCLC. Positive predictive effects of aggressive disease have since been reported with other anti-angiogenic agents (ramucirumab and bevacizumab), while such features may negatively impact on outcomes with nivolumab in nonsquamous NSCLC with low PD-L1 expression. Based on a review of the clinical data, we recommend aggressive nonsquamous NSCLC should be defined by progression within <6–9 months of first-line treatment initiation. Lay abstract: Chemotherapy with platinum-containing drugs was for many years the standard initial treatment for advanced NSCLC. Today's treatment options also include drugs that help the immune system to attack the cancer ('immunotherapies'). These drugs may be used with or without chemotherapy, depending on the molecular profile of the tumor. However, many patients have a fast-growing ('aggressive') form of NSCLC and so gain little benefit from initial chemotherapy. This patient subgroup has often been overlooked in clinical research to date. In this article, we discuss how 'aggressive NSCLC' can be defined and consider how many patients are affected. We also look at the impact of aggressive disease on the effectiveness of other treatments used after initial chemotherapy. Based on a thorough review of the evidence, we recommend that patients who need to change treatment within 6–9 months of starting initial therapy should be defined as having aggressive NSCLC. We hope this definition can help doctors to recognize aggressive tumors and adapt treatment accordingly to improve patients' outcome.